Efektivitas Tata Kelola Pengaduan Masyarakat: Studi Implementasi Kebijakan di Dinas Perindustrian dan Perdagangan Provinsi Jawa Barat - Maura Shalsabila Aderis; Ivan Darmawan; Jovanscha Qisty Adinda (LPPM Universitas Abdurrab, 2026)
Public complaint management is an important instrument in ensuring accountability and the quality of public services. However, in practice, many local government agencies still face obstacles in managing public complaints effectively. This study aims to analyze the effectiveness of public complaint governance at the Department of Industry and Trade of West Java Province using George C. Edward III’s policy implementation theory as an analytical framework.This study employs a qualitative method with a descriptive approach. Data were collected through in-depth interviews, observations, and document analysis, and were analyzed inductively based on four policy implementation variables: communication, resources, disposition, and bureaucratic structure.The findings indicate that public complaint governance has not been implemented effectively. The main obstacles include weak policy transmission and socialization, a mismatch between human resource competencies and assigned tasks, and the lack of internalization of Standard Operating Procedures (SOPs) as operational guidelines. In addition, organizational role distortion occurs due to the transfer of technical complaint handling to the Public Relations unit.This study concludes that strengthening internal regulations and enhancing the capacity of government officials are key prerequisites for realizing accountable and responsive public complaint governance.